Changes in Hepatic Hemodynamics due to Primary Liver Tumours. Issue 4 (1996) - Jakab, F.; Ráth, Z.; Schmal, F.; Nagy, P.; Faller, J.
Abstract : Data regarding the afferent circulation of the liver in patients with primary hepatocellular carcinoma are controversial, we have carried out measurement of hepatic arterial and portal venous flow intraoperatively by transit time ultrasonic volume flowmetry. In patients with primary hepatocellular carcinoma the hepatic artery flow increased to 0.55±0.211 compared with the control value of 0.37±0.102 1/min. (p<0.01). The portal venous flow decreased from 0.61±0.212 l/min, to 0.47±l/min. p<0.01). Due to the opposite changes in the afferent circulation the total hepatic blood flow did not change significantly, compared with controls. The ratio of hepatic arterial flow to portal vein flow increased to 1.239±0.246 in patients with hepatocellular carcinoma, which is double of the control value (0.66±0.259 l/min). After resection this ratio did not change. The resection did not alter hepatic artery or portal venous flow significantly, although the total hepatic blood flow decreased significantly (p<0.01). On the basis of our early results it is possible that the ratio of the two circulations may be to deel measured with doppler ultrasound and provide diagnostic information.